DEVELOPMENT OF DIALECTICAL THINKING IN STUDENTS AS A FACTOR IN IMPROVING THE QUALITY OF HIGHER EDUCATION IN TECHNICAL UNIVERSITIES - Rashchikulina, Elena Nikolayevna; Plugina, Natalya Aleksandrovna; Panova, Lyudmila Petrovna; Kondrashova, Elena Nikolaevna; Bezenkova, Tatyana Aleksandrovna; Mameteva, Olga Sergeevna (Journal of Applied Engineering Science, 2018)
The issue of improving the higher education quality within the framework of gnostic approach is updated in the article against the backdrop of dynamic scientific and technical process development and globalization of economic and social development. The purpose of the article is to develop a structural and logical approach to ensuring dialectical thinking development in students using integrative approach and complementarity method in the process of instruction. A low level of dialectical thinking in students has been revealed as a result of a pedagogical experiment in higher educational institutions of the Russian Federation. Principles, criteria and conditions for improving methodological support have been developed and substantiated through the example of such academic disciplines as ‘Modern Natural Science Concept’ and ‘General Physics’ with the aim to provide cross-curriculum communications and to form integrative concepts. A system of criteria for integrative concepts formedness in students has been reasoned with the use of special exercises of interdisciplinary reflexive supplementary type in the process of instruction. A problem-based developmental programmed exercise aimed at development of dialectical thinking in terms of the above academic disciplines has been elaborated using the complementarity method. Criteria for dialectical thinking development in students have been substantiated. The effectiveness of implementation of the proposed recommendations for the integrative method and the complementarity method application in higher education has been assessed.
Keywords: Integrative Method; Complementarity Method; Dialectical Thinking in Students; Cross-Curriculum Communications; Integrative Concepts; re-development; integrity